The Role of Intercultural Interaction in Community-Based Tourism Man-agement in Nganggring - Lestari, Rini (IHSA Institute, 2024)
This study aims to analyze the role of intercultural interaction in community-based tourism management in Nganggring Tourism Village, Yogyakarta. Through a qualitative approach with a case study method, this study explores how interactions between tourists and local communities contribute to cultural preservation, increasing social cohesion, and economic impacts on local communities. The results show that active participation of tourists in cultural activities, such as local handicrafts and agriculture, not only enriches the tourism experience but also helps preserve traditions and strengthen the cultural identity of the village community. Intense interactions between tourists and local residents also play a role in building closer social relationships, while providing economic benefits through homestays and sales of local products. This study suggests the importance of skills training for local communities, wider tourism promotion, and collaboration with educational institutions and the government to maintain the sustainability of community-based tourism in Nganggring Village. Thus, this management model can be used as a reference for the development of other tourism villages in Indonesia